Morning in refugee health: an introduction for medical students. Issue 2 (15th June 2015) - Duke, Pauline S.; Brunger, Fern; Ohle, Elizabeth
Abstract : Purpose: – Migration is increasing worldwide. health care practitioners must provide care to migrants in a culturally competent manner that is sensitive to cultural, political and economic contexts shaping health and illness. Many studies have provided strong evidence that health providers benefit from training in cross-cultural care. Cultural competence education of medical students during their early learning can begin to address attitudes and responsiveness toward refugees. At Memorial University in Canada, the authors designed "Morning in Refugee Health", an innovative program in cultural competency training for first year medical students in the Clinical Skills and Ethics course. The purpose of this paper is to discuss these issues. Design/methodology/approach: – Here the authors introduce the curriculum and provide the rationale for the specific pedagogical techniques employed, emphasizing the consideration of culture in its relation to political and economic contexts. The authors describe the innovation of training standardized patients (SPs) who are themselves immigrants or refugees. The authors explain how and why the collaboration of community agencies and medical school administration is key to the successful implementation of such a curriculum. Findings: – Medical students benefit from early pre-clinical education in refugee health. Specific attention to community context, SP training, small group format, linkages between clinical skills and medical ethics, medical school administrative and community agency support are essential to development and delivery of this curriculum. As a result of the Morning in Refugee Health, students initiated a community medical outreach project for newly arriving refugees. Originality/value: – The approach is unique in three ways: integration of training in clinical skills and ethics; training of SPs who are themselves immigrants or refugees; and reflection on the political, economic and cultural contexts shaping health and health care.